Magnetic Levitation Technology As An Object Floating Technique In Wooden Craft - Sumino Sumino; Achmad Gilang Romadhon (Institut Seni Indonesia Yogyakarta, 2022)
Research and application of magnetic levitation have been expanded in electric motors, generators, radar monitoring systems, car-door central locks, and metal object towing devices. In the operation, the objects do not touch each other. The use of a magnet-based system that floats objects is called a levitation system. In earlier times, fine art had been comfortable with its structure. Consequently, it is not prepared to deal with electromagnetic technology systems. Magnetic levitation technology is the process of floating objects with a gravitational force that rejects or counteracts each other in a magnetic field. This research aims to provide innovations in applying magnetic levitation in designing fine artworks in Indonesia, mainly wooden crafts. The work was designed with eco-design methods. The magnetic levitation techniques have been widely applied in woodcraft art today. The process of floating objects in the air has the property of rejecting each other's components, while the use of permanent magnets sets the object's position stable. Wood material as an object medium is formed to resemble a flying bird stabilized by magnetic levitation techniques. This wooden crafts experiment featured objects spinning and hovering when exposed to the wind.